Factors facilitating effective knowledge spillovers from foreign to domestic construction firms in Abuja, Nigeria. - Olorunfemi Bamisaye; NAJIMU SAKA; Taiwo Adegbembo (Journal of Construction Project Management and Innovation)
The potential benefits of Foreign Direct Investment (FDI) on the host economy are capital inflows, job creation and most importantly, knowledge spillovers. The purpose of this study was to assess the key factors that facilitate effective knowledge spillovers from foreign construction firms to local construction firms. Data were collected through the use of a well-structured questionnaire. It was administered to construction professionals in both foreign and domestic construction firms in Abuja, Nigeria. The data were analysed using descriptive and inferential statistical tools. It was revealed in the study that ICT, access to finance, the skill of workers and employee motivation were the key factors responsible for effective knowledge spillovers. Hence, it was recommended that domestic firms should fully harness the key factors responsible for effective knowledge spillovers, as this will enable them to widen their knowledge spectrum and not become trapped in their current expertise. Also, the government should make and enforce policies that will encourage knowledge spillovers.